Transporter‐Mediated Hepatic Uptake Plays an Important Role in the Pharmacokinetics and Drug–Drug Interactions of Montelukast. Issue 3 (18th November 2016) - Varma, MV; Kimoto, E; Scialis, R; Bi, Y; Lin, J; Eng, H; Kalgutkar, AS; El‐Kattan, AF; Rodrigues, AD; Tremaine, LM
Abstract : Montelukast, a leukotriene receptor antagonist commonly prescribed for treatment of asthma, is primarily metabolized by cytochrome P450 (CYP)2C8, and has been suggested as a probe substrate for investigating CYP2C8 activity in vivo . We evaluated the quantitative role of hepatic uptake transport in its pharmacokinetics and drug–drug interactions (DDIs). Montelukast was characterized with significant active uptake in human hepatocytes, and showed affinity towards organic anion transporting polypeptides (OATPs) in transfected cell systems. Single‐dose rifampicin, an OATP inhibitor, decreased montelukast clearance in rats and monkeys. Clinical DDIs of montelukast were evaluated using physiologically based pharmacokinetic modeling; and simulation of the interactions with gemfibrozil–CYP2C8 and OATP1B1/1B3 inhibitor, clarithromycin–CYP3A and OATP1B1/1B3 inhibitor, and itraconazole–CYP3A inhibitor, implicated OATPs‐CYP2C8‐CYP2C8 interplay as the primary determinant of montelukast pharmacokinetics. In conclusion, hepatic uptake plays a key role in the pharmacokinetics of montelukast, which should be taken into account when interpreting clinical interactions.